Е-урядування: легальність та легітимність влади інформаційної доби - Яковлева, Лілія (Видавництво Львівської політехніки, 2014)
The article studies the conceptualization of the idea of e-democracy. Determined that the source of the concept of e-democracy advocate the theory of postindustrial, information society and the idea of direct democracy and participatory democracy. By using the historical method was investigated ideological sources of the concept of e-democracy, and thanks to the conceptual approach presented genesis of the concept of e-democracy.
Keywords: е-урядування; інформаційне суспільство; легітимність е-уряду; легальність е-уряду; демократія